Encountering the Medieval in Modern Jewish Thought. - Diamond, James A. (Supplements to the Journal of Jewish Thought and Philosophy Ser., 2012)
How does the "medieval" function as a bearer of Jewish identity in a changing secular world? Each chapter in Encountering the Medieval in Modern Jewish Thought addresses a different Jewish return to the medieval by using a language of renewal.